Kualitas Pelayanan Dalam Pembuatan E-KTP Di Kecamatan Coblong Kota Bandung: service quality in making E-KTPs in Coblong district Bandung city - Agustina, Reza; Fadlika, Rizka; Rifki Zein Al birri, Agustina (Jurnal Administrasi Publik dan Bisnis, 2024)
Improving decision making is just one way to improve service quality; Another is to help officers become better at providing different resources to service management through structured training at different levels. Merely exploiting indications that are intrinsic to the consumer of a service, pleasure with the service as such, is not sufficient to evaluate the efficiency of a public service. Using a number of service quality characteristics, including assurance, direct evidence, empathy, responsiveness, dependability, and communication, this study assesses the quality of E-KTP manufacturing services offered by governments in various regions of Indonesia. Furthermore, this investigation was carried out to identify variables that limit service quality, as evidenced by infrastructure and facilities, service protocols, and personnel competency.